2023
DOI: 10.33182/ml.v20i2.2890
|View full text |Cite
|
Sign up to set email alerts
|

Future Paths in the Study of Migrant Descendants' Citizenship

Abstract: This paper discusses how research related to migrant descendants’ citizenship could potentially benefit from recent critical literature towards migration and citizenship. On the one hand, we discuss how such research focusing on the so-called “second generation” and citizenship could draw from conceptualisations that approach citizenship as everyday practices and as lived experience. On the other hand, we reflect on how such research could benefit from calls to de-migrantize migration scholarship. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Research using a longitudinal approach has shown how context throughout adolescence influences political opinions, as in the case of experienced inequality and desires for wealth redistribution (Roth & Wohlfart, 2018). A belief toward immigrants' acceptance is finally correlated with being descendent of foreigners (Riniolo & Toivanen, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research using a longitudinal approach has shown how context throughout adolescence influences political opinions, as in the case of experienced inequality and desires for wealth redistribution (Roth & Wohlfart, 2018). A belief toward immigrants' acceptance is finally correlated with being descendent of foreigners (Riniolo & Toivanen, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%